Secret conversions to Judaism in early modern Europe - Mulsow, Martin; Popkin, Richard H. (Richard Henry), 1923-2005 (Brill's studies in intellectual history ;, 2004)
This work deals with conversions to Judaism from the 16th to the 18th century. It provides six case studies by scholars on phenomena as crypto-Judaism, "judaizing", reversion of Jewish-Christian converts and secret conversion of non-Jewish Christians for intellectual reasons.